Pengaruh Dosis Em4 Pada Biomas Jerami Terhadap Peningkatan Kapasitas Simpan Air Tanah Pada Lahan Sawah - Kusuma, Oktavianus Erwin Chrisdana; Tika, I Wayan; Arda, Gede (Innovative: Journal Of Social Science Research, 2025)
Soil water holding capacity is the ability of the soil to retain water and provide water for plants. Factors that affect soil water capacity include effective soil depth, soil particle size distribution, and soil organic matter content. The purpose of this study was to determine the effect of straw biomass utilization on efforts to increase groundwater storage capacity in agricultural land. This study used four treatments. (J0) Provision of straw without molasses, (J6) provision of straw plus molasses with a dose of 6 liters/ha, (J12) provision of straw plus molasses with a dose of 12 liters/ha, and (J18) provision of straw plus molasses with a dose of 18 liters/ha. The research design used was a Completely Randomized Design. The number of sample units in the treatment was the provision of straw without a dose of 3 rings of molasses, a dose of 6 liters/ha of 3 rings of soil, a dose of 12 liters/ha of 3 rings of soil, and a dose of 18 liters/ha of 3 rings of soil. Each treatment was repeated three times. Measurement of groundwater holding capacity data was carried out by calculating the percentage of water content that could be stored in each sample. The average percentage of water content in the soil, straw administration without molasses dose was 16.65%, dose of 6 liters/ha was 27,91 %, dose of 12 liters/ha was 29.89%, and dose of 18 liters/ha was 28.11%.